Tuning the mechanical properties of weakly phase-separated olefin block copolymer by establishing co-crystallization structure with the aid of linear polyethylene: the dependence on molecular chain length. Issue 21 (17th May 2017) - Zhao, Yongsheng; Si, Lianmeng; Wang, Lamei; Dang, Wanbin; Bao, Jingjing; Lu, Zhaoqing; Zhang, Meiyun
Abstract : Co-crystallization structure formed by blending. Abstract : Olefin block copolymer (OBC) is a novel thermoplastic elastomer possessing multiblock features but has limited mechanical property due to a partial-branched hard segment. In this study, olefin block copolymer was blended with linear polyethylene (PE) with varying molecular chain lengths in order to investigate the influence of linear polyethylene on the mechanical performance, crystallization behavior and crystalline morphology of OBCs. It was found that the addition of PE is in favor of enhancing the mechanical properties of OBC. The long PE chains are more effective for reinforcing, and thus a rubber-to-plastic transition occurs when a large amount of ultra-long PE chains is introduced. At the same time, a small addition of PEs can be fully miscible with OBC and induces co-crystallization behavior. In this way, the tie effect from the PE chains was gradually enhanced particularly for OBC/PE samples blended with ultra-long chains. In addition, crystal orientation can be further enhanced in OBC/PE blends when shear flow is applied. More interestingly, shish–kebab structure is achieved where ultra-long PE chains act as the shish, while hard segments of OBC grow epitaxially on the shish to form kebabs. Our study shows a highly effective self-reinforcing mechanism through the regulation of crystalline morphologies for OBC multiblock copolymers, in which the unique shish–kebab structure was successfully established based on an entangled system.